(3JfejI GdehGQO GdHTQjI (B/s - (3GdXGgQ, fYje EHQGgjes ((3YeGf(B: s (3YGde GdcJH GdMOjK(B, s, 2009)
(3GdeONd Edi JfejI GdehGQO GdHTQjI,JfejI GdehGQO GdHTQjI hHfGA GSJQGJjLjGJgG GdeYGUQI,GdEOGQI GdESJQGJjLjI ddCaQGO,JMdjd GdYhGed hGdehGQO GdHTQjI,EOGQI GdQhGJH hGdCLhQ hGdMhGaR,GSJQGJjLjI JOQjH hJfejI GdehGQO GdHTQjI,bVGjG heTGcd eYGUQI aj EOGQI GdCaQGOs
(3HHdjhZQGajG(B:(3U U(B.342-345s
Keywords: (3EOGQI GdCaQGOs; (3JfejIs